Extremal values of Merrifield-Simmons index for trees with two branching vertices (2018)
In this paper we find trees with minimal and maximal Merrifield-Simmons index over the set Ω (n, 2) of all trees with n vertices and 2 branching vertices, and also over the subset Ω t (n, 2) of all trees in Ω (n, 2) such that the branching vertices are connected by the path Pt.